Directive Speech Act in Moluccan Children Traditional Game Songs in Maluku - Mariana Lewier; Merlyn Rutumalessy; Viona Sapulette (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Up to the present time, there are still many children games played with their respective accompanying songs by young children in Maluku. The lyrics of these children songs can be categorized as one form of texts that can be analyzed in terms of language aspects. This paper discusses directive speech acts contained in the children songs-attached games in Maluku. The purpose of this paper is to describe the various acts of directive speech, the social-cultural context that embodies it, and the level of politeness they may carry. The approach used was pragmatic approach, specifically the framework of speech act theory. The data used in this study was children songs in Ambon-Maluku, both oral and written data containing directive statements. Data analysis was done by interpreting, making inferences, and presenting it in the form of descriptive analysis. Descriptive analysis is intended to describe, provide an overview and identify the relationship between the phenomena being studied. The directive act of speech contained in the children game songs in Maluku can be categorized as direct or indirect. The direct way of directive speech acts is used for requesting, ordering, inviting, and forbidding, while the indirect way is preferred than imperative mode by using interrogative sentence, news report, and a particular request statement. Thus, through this analysis, we may come to an understanding of the dynamics of socio-cultural realm that underlies the presence of children game traditions in Maluku.